Basolateral potassium (IK(Ca)) channel inhibition prevents increased colonic permeability induced by chemical hypoxia - Loganathan, A. (American Physiological Society, 2011)
Major liver resection is associated with impaired intestinal perfusion and intestinal ischemia, resulting in decreased mucosal integrity, increased bacterial translocation, and an increased risk of postoperative sepsis. However, the mechanism by which ischemia impairs intestinal mucosal integrity is unclear. We therefore evaluated the role of Ca(2+)-sensitive, intermediate-conductance (IK(Ca)) basolateral potassium channels in enhanced intestinal permeability secondary to chemical hypoxia. The effects of chemical hypoxia induced by 100 μM dinitrophenol (DNP) and 5 mM deoxyglucose (DG) on basolateral IK(Ca) channel activity and whole cell conductance in intact human colonic crypts, and paracellular permeability (G(S)) in isolated colonic sheets, were determined by patch-clamp recording and transepithelial electrical measurements, respectively. DNP and DG rapidly stimulated IK(Ca) channels in cell-attached basolateral membrane patches and elicited a twofold increase (P = 0.004) in whole cell conductance in amphotericin B-permeabilized membrane patches, changes that were inhibited by the specific IK(Ca) channel blockers TRAM-34 (100 nM) and clotrimazole (CLT; 10 μM). In colonic sheets apically permeabilized with nystatin, DNP elicited a twofold increase (P = 0.005) in G(S), which was largely inhibited by the serosal addition of 50 μM CLT. We conclude that, in intestinal epithelia, chemical hypoxia increases G(S) through a mechanism involving basolateral IK(Ca) channel activation. Basolateral IK(Ca) channel inhibition may prevent or limit increased intestinal permeability during liver surgery.